Tinjauan Pasal UU ITE Serta Ancaman terhadap Aksi Revenge Porn dalam Film Like and Share (2022) - Hutagaol, Jessica Ariana (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
In now days, social media is not something strange in our society. Lots of people use their mobile phone to access social media from various platforms for uploading or communicating matter. In accessing social media, there are certain untold rules and norms applied. However, this matter does not rule out the possibility for people to become a victim of cyber crimes, one of those kind of crimes is revenge porn. Revenge porn is an action where the perpetrator posted intimate photos or videos of the victim widely as a form of revenge. This action exactly occurs in a movie tthat itled "Like and Share". Ths is research will review the motives for the perpetrator's actions and the articles in the ITE Law that underlie the crime. This main problem will be researched using qualitative methods and a normative juridical approach. Apart from that, this research will analyze which criminal code that can protecst victims' rights